Design Shortcomings of the Headwork and Water Distribution and Control Facilities of the Canal Irrigation Systems of Ilocos Norte, Philippines - David, Wilfredo Pineda; de los Reyes, Mona Liza F.; Villano, Manolo G.; Fajardo, Arthur L. (2012)
The performances of 2 National Irrigation Systems (NIS), 6 Communal Irrigation Systems (CIS) and 2 Small Water Impounding Projects (SWIP) in Ilocos Norte were evaluated from the standpoint of their dry season irrigation intensity, which is defined as the ratio of the actual area irrigated during the dry season to the irrigation service area. Some important design criteria and features of these sample irrigation systems were investigated to help explain their performances. Field observations of the existing physical structures of these systems were carried out to assess their overall capacity to convey and distribute the required water efficiently. Frequency analysis of the maximum rainfall totals measured at the nearest weather station during the period 1976–2005 was carried out to gain insights on the return periods of the 1-d, 2-d, 3-d and 4-d rainfall totals brought about by a typhoon that heavily damaged the headworks of two of the sample irrigation systems. The study showed an average dry season cropping intensity in crop year 2005–2006 of only 27%. This very low irrigation intensity can be partly attributed to the extensive damage of the dam of the Madongan River Irrigation System (RIS), the largest irrigation system within the province. The results of frequency analysis indicated that the 1-d, 2-d, 3-d and 4-d rainfall totals had associated return periods ranging only from 2.4 to 4.3 yr. The poor performance of the irrigation systems studied can be traced to their design shortcomings and undesirable design features. The potentials for improvements in hydraulic structures were evident.
Keywords: Irrigation canals & flumes; Water distribution